Cell-Free Expression and Photo-Crosslinking of the Human Neuropeptide Y2 Receptor - Kögler, Lisa Maria; Stichel, Jan; Kaiser, Anette; Beck-Sickinger, Annette G. (Frontiers in Pharmacology, 2019)
G protein-coupled receptors (GPCRs) represent a large family of different proteins, which are involved in physiological processes throughout the entire body. Furthermore, they represent important drug targets. For rational drug design, it is important to get further insights into the binding mode of endogenous ligands and therapeutic agents at the respective target receptors. However, structural investigations usually require homogenous, solubilized and functional receptors, which is still challenging. Cell-free expression methods have emerged in the last years and many different proteins are successfully expressed, including hydrophobic membrane proteins like GPCRs. In this work, an Escherichia coli based cell-free expression system was used to express the neuropeptide Y2 receptor (Y2R) for structural investigations. This GPCR was produced in two different variants, a protein fusion protein with C-terminal enhanced green fluorescent and a cysteine deficient variant. In order to obtain soluble receptors, the expression was performed in the presence of mild detergents, either Brij-35 or Brij-58, which led to high amounts of soluble receptor. Furthermore, the influence of temperature, pH value and additives on protein expression and solubilization was tested. For functional and structural investigations, the receptors were expressed at 37 °C, pH 7.4 in the presence of 1 mM oxidized and 5 mM reduced glutathione. The expressed receptors were purified by ligand affinity chromatography and functionality of Y2R_cysteine_deficient was verified by a homogenous binding assay. Finally, photo-crosslinking studies were performed between cell-free expressed Y2R_cysteine_deficient and a neuropeptide Y analogue containing the photoactive, unnatural amino acid p-benzoyl-phenylalanine at position 27 and biotin at position 22 for purification. After enzymatic digestion, fragments of the crosslinked receptor were identified by mass spectrometry. Our findings demonstrate that, in contrast to Y1R, neuropeptide Y position 27 remains flexible when bound to Y2R. These results are in agreement with the suggested binding mode of neuropeptide Y at Y2R.